2005
DOI: 10.1007/s00125-005-0008-3
|View full text |Cite
|
Sign up to set email alerts
|

Primary and immortalised human pancreatic islet endothelial cells: phenotypic and immunological characterisation

Abstract: Aims/hypothesis: Studies on the biology of the microvascular endothelial cells (MECs) that surround and penetrate the pancreatic islets are hampered by difficulties in isolating and culturing large numbers of pure cells. We aimed to morphologically and functionally characterise primary MECs purified and cultured from human islets, and to establish a simian virus 40 (SV40)-immortalised cell line from these primary cultures. Materials and methods: Human islet MECs were extracted and purified using anti-CD105 coa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
12
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 51 publications
3
12
0
Order By: Relevance
“…Flow cytometry demonstrated that they expressed cell surface antigens typically associated with MSCs, including CD105, CD13, CD44, CD73 and CD90, but did not express cell surface antigens characteristic of MECs, including CD31, CD34, CD69, CD117 and vascular endothelial growth factor receptor-2 [7]. Our cells were capable of expansion in standard EC culture medium supplemented with EC growth factors and, in common with both macro-and microvascular ECs [8], they formed capillary-like tubes when maintained on Matrigel (BD Biosciences, Oxford, UK; not shown), as has been reported previously for cell populations isolated from human islets on the basis of CD105 expression [2]. Despite this, the morphology, cell surface marker/receptor expression and multipotency of our cell isolates are not consistent with an islet MEC phenotype.…”
Section: Ecsupporting
confidence: 80%
See 2 more Smart Citations
“…Flow cytometry demonstrated that they expressed cell surface antigens typically associated with MSCs, including CD105, CD13, CD44, CD73 and CD90, but did not express cell surface antigens characteristic of MECs, including CD31, CD34, CD69, CD117 and vascular endothelial growth factor receptor-2 [7]. Our cells were capable of expansion in standard EC culture medium supplemented with EC growth factors and, in common with both macro-and microvascular ECs [8], they formed capillary-like tubes when maintained on Matrigel (BD Biosciences, Oxford, UK; not shown), as has been reported previously for cell populations isolated from human islets on the basis of CD105 expression [2]. Despite this, the morphology, cell surface marker/receptor expression and multipotency of our cell isolates are not consistent with an islet MEC phenotype.…”
Section: Ecsupporting
confidence: 80%
“…Macro-and microvascular endothelial cells (ECs) are certainly CD105-positive, but this accessory receptor is also highly expressed by a range of other cell types including bone marrow-and tissue-derived mesenchymal stromal cell (MSC)-like populations. In accordance with this, we have recently isolated from human islets, and expanded in vitro, a population of CD105-expressing cells that are clearly not MECs, but which share phenotypic characteristics with other cells that have been immuno-isolated on the basis of CD105 expression and identified as islet MECs for in vitro studies [1][2][3][4][5].Our cell population was isolated and expanded essentially as described for MSCs [6]. Briefly, human islets (obtained from the King's College London Human Islet Isolation Unit, with appropriate ethics approval) were dissociated by incubation in 0.02% (wt/vol.)…”
mentioning
confidence: 70%
See 1 more Smart Citation
“…25 Cells were grown until confluent, washed twice with Hanks' balanced salt solution, and dispersed with trypsin/EDTA when subcultured in appropriate flasks or plates, depending on the experiment performed. When cultured under high-glucose conditions, complete medium was adjusted to 14 mmol/L or 28 mmol/L glucose (Sigma) to assess the diverse effects of glucose concentration and treatment duration.…”
Section: Islet Endothelial Cell Culture Conditionsmentioning
confidence: 99%
“…CD105 has been used to recover endothelial cells from several tissues, in combination with critical culture conditions, specifically endothelial basal medium (EBM) supplemented with specific endothelial growth factors [2,3]. This strategy generates, from isolated islets, cells expressing endothelial markers such as von Willebrand factor, CD31, vascular endothelial (VE)-cadherin, TNF-α-upregulated E-selectin, induced HLA-DR molecules [4] and co-stimulatory molecules such as CD86 and inducible T-cell co-stimulator (ICOS) ligand [5], together with the expression of a panel of genes related to endothelial biology and the secretion of NO and vascular endothelial growth factor (VEGF)-A [3,6]. This islet endothelium shows unique characteristics such as surface fenestrations and the presence of α-1 proteinase inhibitor (also known as Api or α-1 antitrypsin) and nephrin, a highly specific barrier protein [6].…”
Section: Mscmentioning
confidence: 99%